[tex]p=2,\ \ a=\frac{1}{5},\ \ c=1,\ \ g=\frac{1}{3} \\\\5p-p^2=5*2-2^2=10-4=6\\\\ 5a-a^2=5*\frac{1}{5}-(\frac{1}{5})^2=1-\frac{1}{25}=\frac{24}{25}\\\\5c-c^2=5*1-1^2=5-1=4\\\\5g-g^2=5*(\frac{1}{3})-(\frac{1}{3})^2=\frac{5}{3}-\frac{1}{9}=\frac{15}{9}-\frac{1}{9}=\frac{14}{9}=1\frac{5}{9}[/tex]
[tex](a-\frac{1}{10}):3=( \frac{1}{5}-\frac{1}{10})*\frac{1}{3}=(\frac{2 }{10}-\frac{1}{10})*\frac{1}{3}=\frac{1}{10}*\frac{1}{3}=\frac{1 }{30} \\\\(p-\frac{1}{10}):2=(2-\frac{1}{10})*\frac{1}{2}=(\frac{20}{10}-\frac{1}{10})*\frac{1}{2}=\frac{19}{10}*\frac{1}{2}=\frac{19}{20}\\\\ (c-\frac{2}{6}):6=(1-\frac{2}{6})*\frac{1}{6}= \frac{\not{4}^2}{6}*\frac{1}{\not{6}^3} =\frac{2}{18}=\frac{1}{9}[/tex]
[tex](g-\frac{2}{6}):14=(\frac{1}{3}-\frac{2}{6})*\frac{1}{14}=(\frac{2}{6}-\frac{2}{6})*\frac{1}{14}= 0*\frac{1}{14}=0[/tex]